The Influence of GLOBE Culture Dimensions on Entrepreneurial Orientation in Tourism and Medical Service Sectors in Serbia - Nedeljković Knežević, Milena; Pavluković, Vanja (Geographica Pannonica, 2020)
The main objective of the research is to examine, for the first time, the influence of dimensions of culture according to the GLOBE model on the dimensions of entrepreneurial orientation. The research sample belongs to the service sector within the transitional society of Serbia, i.e. tourism and medical sector, which are linked through the ever-growing health tourism industry. Different influences of dimensions of culture (uncertainty avoidance, performance orientation, group collectivism, assertiveness and gender equality) on dimensions of entrepreneurial orientation (work ethic. innovativeness, empathy, autonomy and risk readiness) are confirmed. The obtained results are important for defining the cultural framework which influences the development of entrepreneurial activities within tourism and health service sectors in Serbia.